MIGRATION PATTERN OF YOUNG PEOPLE IN RURAL (Case Study of young people in Ciasmara Village, Pamijahan District Bogor Regency) - Roni Jayawinangun; Muslim . (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
Low natural resources that support the economy and the inability of people in access is one factor that makes many villagers unable to accumulate capital. Mobilization out of the village is the most logical step taken by villagers to keep them alive. The existence of job opportunities elsewhere and the condition of the village that is no longer conducive will affect the mobility patterns of household members in the village. This research aimed:1) Identify portraits of young villagers on the potential of Ciasmara Village Resources; 2) Identify the driving factors that make young people in rural areas migrate to the city. Quantitative method was used to processed the data using descriptive analysis to know the characteristics of respondents the data processed using the average score is the perception of youth against the village resources and the factors driving and pulling migration. This research found thatPortrait of young people towards Ciasmara Village Resources is generally considered good. In general the attraction of the City is greater than the appeal of the Village. There are four indicators of towing power of the City that is high salaries, the number of job options, the opening of vacancies and work more than one.